The Natural History of Metabolic Comorbidities in Turner Syndrome from Childhood to Early Adulthood: Comparison between 45,X Monosomy and Other Karyotypes - Lebenthal, Yael; Levy, Sigal; Sofrin-Drucker, Efrat; Nagelberg, Nessia; Weintrob, Naomi; Shalitin, Shlomit; de Vries, Liat; Tenenbaum, Ariel; Phillip, Moshe; Lazar, Liora (Frontiers in Endocrinology, 2018)
Objective Patients with Turner syndrome (TS) are at increased risk for metabolic disorders. We aimed to delineate the occurrence and evolution of metabolic comorbidities in TS patients and to determine whether these differ in 45,X monosomy and other karyotypes. Methods A longitudinal and cross-sectional retrospective cohort study was conducted in a tertiary pediatric endocrine unit during 1980–2016. Ninety-eight TS patients, 30 with 45,X monosomy were followed from childhood to early adulthood. Outcome measures included weight status, blood pressure (BP), glucose metabolism, and lipid profile. Results Longitudinal analysis showed a significant change in body mass index (BMI) percentiles over time [F(3,115) = 4.8, P = 0.003]. Age was associated with evolution of elevated BP [systolic BP: odds ratio (OR) = 0.91, P = 0.003; diastolic BP: OR = 0.93, P = 0.023], impaired glucose metabolism (HbA1c: OR = 1.08, P = 0.029; impaired glucose tolerance: OR = 1.12, P = 0.029), and abnormal lipid profile (cholesterol: OR = 1.06, P = 0.01; low-density lipoprotein cholesterol: OR = 1.07, P = 0.041; high-density lipoprotein cholesterol: OR = 1.07, P = 0.033). The occurrence of metabolic comorbidities was similar in 45,X monosomy and other karyotypes. Coexistence of multiple metabolic comorbidities was significantly higher in 45,X monosomy [F(1,72) = 4.81, P = 0.032]. BMI percentiles were positively correlated with metabolic comorbidities (occurrence and number) in each patient (r = 0.35, P = 0.002 and r = 0.383, P = 0.001, respectively). Conclusion Our longitudinal study provides unique insights into the evolution of weight gain and metabolic disorders from childhood to early adulthood in TS patients. Since overweight and increasing age aggravate the risk for metabolic comorbidities, careful surveillance is warranted to prevent and control obesity already from childhood. The more prominent clustering of metabolic comorbidities in 45,X monosomy underscores the importance of a more vigorous intervention in this group.